Slc7a11 stimulates glutathione synthesis to preserve fatty acid metabolism in primary hepatocytes - Yifan Liu; Kaimin Wu; Yinkun Fu; Wenyan Li; Xu-Yun Zhao (Taylor & Francis Group, 2023)
ABSTRACTPrimary hepatocytes are widely used as a tool for studying metabolic function and regulation in the liver. However, the metabolic properties of primary hepatocytes are gradually lost after isolation. Here, we illustrated that fatty acid metabolism is the major compromised metabolic process in isolated primary hepatocytes, along with drastically decreased GSH and ROS content, while lipid peroxidation is increased. Gain- and loss-of-function studies revealed that Slc7a11 expression is critical in maintaining fatty acid metabolism and facilitating hormone-induced fatty acid metabolic events, which is synergistic with dexamethasone treatment. Intriguingly, Slc7a11 expression and dexamethasone treatment cooperatively upregulated AKT and AMPK signaling and mitochondrial complex expression in primary hepatocytes. Furthermore, direct treatment with reduced GSH or inhibition of ferroptosis is sufficient to drive protective effects on fatty acid metabolism in primary hepatocytes. Our results demonstrate that Slc7a11 expression in isolated primary hepatocytes induces GSH production, which protects against ferroptosis, to increase fatty acid metabolic gene expression, AKT and AMPK signaling and mitochondrial function in synergy with dexamethasone treatment, thereby efficiently preserving primary hepatocyte metabolic signatures, thus providing a promising approach to better reserve primary hepatocyte metabolic activities after isolation to potentially improve the understanding of liver biological functions from studies using primary hepatocytes.